An epidemiological study of pattern of dermatoses in paediatric age group at a tertiary care teaching hospital in South India - Mavoori, Archana; Sriram, Deepthi; Pamar, Sneha; Bala, Sudha (International Journal of Research in Dermatology, 2020)
Background: Various dermatoses like infections and infestations and other non-infective dermatoses like atopic eczema, pigmentary disorders, papulo-squamous disorders, hair disorders, genetic disorders, hemangiomas etc. affect children causing significant morbidity. The pattern of dermatoses varies from place to place due to differences in geography, climate, culture and socio-economic background. Prevalence of pediatric dermatoses in India are around 9% to 35%. This study is undertaken to know the pattern, incidence, prevalence, contributing factors and prognosis of dermatoses affecting paediatric age group attending Dermatology outpatient department in tertiary health teaching hospital in South India. Methods: This is a prospective study; various skin disorders were studied in 1360 paediatric patients up to 18 years of age were studied for a period of 12 months from September 2017 to October 2018. Demographic data, general, systemic and cutaneous examination findings were recorded in a proforma for analysis and interpretation of data. Results: There were 762 boys and 598 girls in total 1360 study population. The most common dermatoses were eczematous eruptions and dermatitis (22.57%), infections and infestations (20.8%%), infestations (18.96%), hypersensitivity disorders (6.91%). The study showed no statistical differences between sex and age. Conclusions: This study on epidemiological and clinical patterns emphasizes the need on training the management of common paediatric dermatoses to dermatologists, paediatricians for early treatment. Proper implementation of child health programmes and awareness programmes can be done based on such data or to treat them appropriately.